Health and well-being in the crisis - Nikos Askitas; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2011)
The internet has become an important data source for the Social Sciences because these data are available without lags, can be regarded as involuntary surveys and hence have no observer effect, can be geo-labeled, are available for countries across the globe and can be viewed in continuous time scales from the micro to the macro level. The paper uses internet search data to document how the great economic crisis has affected people's well-being and health studying the US, Germany and a cross section of the G8 countries. We investigate two types of searches which capture self-diagnosis and treatment respectively: those that contain the words symptoms and side effects. Significant spikes for both types of searches in all three areas (US, Germany and the G8) are found, which are coincident with the crisis and its contagion timeline. An array of due diligence checks are performed and a number of alternative hypotheses are excluded to confirm that the search spikes imply an increase in malaise.
urn:nbn:de:101:1-201104134376
Keywords: C81; E32; I1; L86; 330; well-being; symptoms; side effects; Gallup; economic crisis; financial crisis; ill-being; Lebensqualität; Gesundheit; Wirtschaftskrise; Finanzmarktkrise; Internet; Suchmaschine; USA; Deutschland; G-8-Staaten